2019
DOI: 10.1108/jea-08-2018-0144
|View full text |Cite
|
Sign up to set email alerts
|

School principals’ systems thinking: antecedents and consequences

Abstract: Purpose Today’s educational complexities require principals to adopt a more systemic perspective toward school management. Although research has emphasized the benefits associated with the holistic perspective of systems thinking, research in the educational field has been limited. The purpose of this paper is to investigate the mediating role of principals’ systems thinking (PST) in the relationships between instructional leadership (IL) and subject coordinators’ organizational commitment and job satisfaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…A school is an inherently complex organization, involving a vast number of interacting functions, people, and purposes (Crick et al, 2017). School faculty members who are facing educational challenges may benefit from ST’s holistic perspective as it emphasizes understanding the system as a whole before studying its parts, while simultaneously considering an array of influencing factors (Benoliel et al, 2019). The attempt to conceptualize a more holistic framework of ST in the school organization (Colleague and Author 2, 2014, 2017) has yielded four core characteristics: (1) seeing wholes ; (2) adopting a multidimensional view ; (3) influencing indirectly ; and (4) evaluating significance .…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…A school is an inherently complex organization, involving a vast number of interacting functions, people, and purposes (Crick et al, 2017). School faculty members who are facing educational challenges may benefit from ST’s holistic perspective as it emphasizes understanding the system as a whole before studying its parts, while simultaneously considering an array of influencing factors (Benoliel et al, 2019). The attempt to conceptualize a more holistic framework of ST in the school organization (Colleague and Author 2, 2014, 2017) has yielded four core characteristics: (1) seeing wholes ; (2) adopting a multidimensional view ; (3) influencing indirectly ; and (4) evaluating significance .…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…A growing body of research shows that PST offers a variety of potential benefits to the overall school organization and to its employees. In this regard, PST was found to create a positive work environment for school staff facilitating job satisfaction and organizational commitment (Benoliel et al , 2019; Nadav et al , 2020).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…PST includes four major activities, namely adopting a multidimensional view, openness to a variety of opinions, leading wholes and evaluating significance , through which principals apply systems thinking (ST) in their schools. Several studies have demonstrated how PST can yield a number of positive effects, including school change and effectiveness as well as improved attitudes toward their job among teachers (Benoliel et al ., 2019; McGurk and Pearson, 2018; Nadav et al ., 2020; Shaked et al ., 2018). Yet, educational leadership research has stressed that leadership is not solely embedded in formal roles but often emerges from relationships between individuals (Lu and Hallinger, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, principals' sense-making is situated in multiple sociocultural contexts; therefore future research should explore how principals' personal history and experience might shape their CC while navigating their schools through change processes (Weick and Sutcliffe, 2007). Viewed from the lens of organizational outcomes, it has been found that principals' cognitive flexibility strengthens the collective efficacy beliefs of their teachers, thereby increasing the latter's willingness to cope with educational changes (Benoliel et al , 2019).…”
Section: Limitations and Future Explorationsmentioning
confidence: 99%